2014
DOI: 10.1093/mnras/stt2330
|View full text |Cite
|
Sign up to set email alerts
|

The multiwavelength polarization of Cygnus X–1

Abstract: Polarization measurements of the microquasar Cygnus X-1 exist at γ-ray, X-ray, UV, optical and radio frequencies. The γ-ray emission has been shown to be highly linearly polarized. Here, we present new infrared polarimetric data of Cygnus X-1 taken with the 10.4-m Gran Telescopio Canarias and the 4.2-m William Herschel Telescope. We show that the broadband, radio to γ-ray flux spectrum and polarization spectrum in the hard state are largely consistent with a simple phenomenological model of a strongly polarize… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
52
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 132 publications
(197 reference statements)
1
52
0
Order By: Relevance
“…The polarization of 8.0±2.5 per cent implies the magnetic field in the region of the jet near its base is moderately tangled. However, the FLP is fairly high for LMXB jets, being comparable to that measured in Cyg X-2 (Shahbaz et al 2008), lower than 4U 0614+09 (if the disc is unpolarized in that source; Baglio et al 2014b) and much lower than Cyg X-1 (Laurent et al 2011;Russell & Shahbaz 2014;Rodriguez et al 2015), but higher than GX 339-4, Sco X-1, GRO J1655-40 and XTE J1550-564 (Shahbaz et al 2008;Russell et al 2011;Chaty et al 2011). The length of the observations implies a continuously launched (stable on long timescales), highly variable (on short timescales) jet in Swift J1357.2-0933, which has a moderately tangled magnetic field close to the jet base.…”
Section: Swift J13572-0933mentioning
confidence: 50%
See 2 more Smart Citations
“…The polarization of 8.0±2.5 per cent implies the magnetic field in the region of the jet near its base is moderately tangled. However, the FLP is fairly high for LMXB jets, being comparable to that measured in Cyg X-2 (Shahbaz et al 2008), lower than 4U 0614+09 (if the disc is unpolarized in that source; Baglio et al 2014b) and much lower than Cyg X-1 (Laurent et al 2011;Russell & Shahbaz 2014;Rodriguez et al 2015), but higher than GX 339-4, Sco X-1, GRO J1655-40 and XTE J1550-564 (Shahbaz et al 2008;Russell et al 2011;Chaty et al 2011). The length of the observations implies a continuously launched (stable on long timescales), highly variable (on short timescales) jet in Swift J1357.2-0933, which has a moderately tangled magnetic field close to the jet base.…”
Section: Swift J13572-0933mentioning
confidence: 50%
“…These measurements have so far suggested that the magnetic fields near the jet base are largely tangled, chaotic and on average, aligned with the jet axis. One exception is Cyg X-1, which appears to have a highly ordered, stable magnetic field near its jet base that is perpendicular to the axis of the jet (Russell & Shahbaz 2014;Rodriguez et al 2015), and V404 Cyg which had flares of low level polarization, with the magnetic field also perpendicular to the jet axis (Shahbaz et al 2016). These levels of polarization are similar to those often seen from LMXB jets at radio frequencies during the hard state, although higher levels (tens of per cent) of radio polarization have been detected, especially during spectral state transitions when discrete ejections are launched (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…, Fender 2006), where a relatively low level of polarization is associated with synchrotron process in the jet. Similar to the studies for multi-wavelength spectral energy distributions (SEDs), it is more inter-esting to study multi-wavelength polarization properties (e.g., Russell & Shahbaz 2014 for a recent work on the microquasar Cygnus X-1). Recently, Laurent et al (2011) observed strong polarization, 67 ± 30%, of the high-energy radiation of Cygnus X-1, between 400 keV and 2 MeV (so-called MeV tail), using the International Gamma-Ray Astrophysics Laboratory Imager on board the Integral satellite (INTEGRAL/IBIS).…”
mentioning
confidence: 99%
“…Producing such a high polarization at MeV tail was claimed as the synchrotron emission of relativistic electrons in the jet due to a uniform (ordered), large-scale magnetic field configuration (Laurent et al 2011;Jourdain et al 2012;Russell & Shahbaz 2014;Rodriguez et al 2015). Alternatively, it has been proposed that a hot accretion flow, which requires monodirection motion of relativistic electrons along highly ordered magnetic fields in the inner regions of the accretion flow (Veledina et al 2013), or a hot, highly magnetized plasma corona around the black hole, where hadron and lepton interacting with matter and magnetic fields are invoked, may produce the highly polarized emission at MeV tail (Romero et al 2014).…”
mentioning
confidence: 99%